Relationship of Parenting and Social Support for Working Single Mothers on the Provision of Balanced Nutrition and Nutritional Status of Early Childhood in Coastal Areas - Nur Endah Sary, Yessy (Al-Athfal: Jurnal Pendidikan Anak, 2020)
This study aimed to analyze parenting and social support relationships by working single mothers on balanced nutritious feeding and early childhood nutritional status. This is quantitative research with a cross-sectional design. This research was conducted in the coastal area of the Probolinggo Regency, consisting of 16 sub-districts. The population in this study was 247 single mothers who worked and had 3-year-old children. The sampling technique of this research is simple random sampling. The final sample in this study was 219 people. A short questionnaire measured the sociodemographic data of research respondents (age, last education, and maternal work). Questionnaires measured data on parenting and social support variables. A food recall sheet measured data on balanced nutritious feeding variables to see the food the mother gave to her child within a month. Nutritional status variable data is recorded using the observation sheet. The data analysis technique in this study was logistic regression. The results showed a link between parenting and social support by single mothers who work with balanced nutritious feeding and early childhood nutritional status in coastal areas. From the results of this study, it can be concluded that health education is needed for mothers who have children in early childhood to help them solve the problems they experience when knowing their child is malnourished. Therefore, cross-sectoral cooperation is needed to provide sustainable health education.